To solve the equation, we'll follow the steps below:
1. Distribute the -2 to the terms inside the parentheses: -6x + 30 - 25 = 35.
2. Simplify the expression by combining like terms: -6x + 5 = 35.
3. Subtract 5 from both sides of the equation to isolate the variable term: -6x = 30.
4. Divide both sides of the equation by -6 to solve for x: x = 30 / -6.
5. Simplify the right side of the equation: x = -5.
Therefore, the solution to the equation -2(3x-15) - 25 = 35 is x = -5.
−2(3x−15)−25=35
1 answer